.28x+4x=-8.56

Simple and best practice solution for .28x+4x=-8.56 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .28x+4x=-8.56 equation:


Simplifying
0.28x + 4x = -8.56

Combine like terms: 0.28x + 4x = 4.28x
4.28x = -8.56

Solving
4.28x = -8.56

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '4.28'.
x = -2

Simplifying
x = -2

See similar equations:

| x^2+20-1360=0 | | .6x+1=19 | | X-13/3 | | 3/4(x-7)^2 | | 20(3r-27)=3(5r+45) | | 3x^2+20x+7=-4x^2+4x+24 | | 6x^2+2x=-7x | | -28.73+(-42.21)=x | | -3.4x+5.1=-22.1 | | (k+4)(k-3)=0 | | 3x*3+x*2=75x+25 | | -28.73+(-42.21)= | | 35/28 | | 3x*3+x*2=75+25 | | 3y+5n+8= | | 15+(-47)=x | | abyse=sb | | -4(y-9)=2y+12 | | (10-3x)*((4x^2)-20x+25)=((x^2)-8x+16)*(2x-5) | | (7x-3)(7x-3)=0 | | -9x+60x=6x | | (-8x^7y)(x^3y^7)=0 | | -9x+60=6x | | (1/7)(1/7)(1/7) | | (2k^3)^4/4k^5 | | 6x-23=14x+49 | | (8x+7)(x^2-4x+1)=0 | | 20x+16=94 | | 4x^2+24x+19=0 | | 4x^2+24+19=0 | | 8x+13=109 | | 7/12*y-1/4=2y-5/3 |

Equations solver categories